Modeling of the break process to improve tomato paste production quality : a thesis presented in partial fulfilment for the degree of Master of Engineering in Bioprocess at Massey University - Srichantra, Arunee (Massey University, 2002)
The pectic enzyme, Pectinmethylesterase (PE) and Polygalacturonase I and II (PGI and PGII), in the tomato fruit released after crushing during tomato processing reduce the viscosity of tomato paste by breaking down the insoluble pectin in the cell wall. To achieve higher viscosity tomato paste, the cold break (<60°C) or hot break (>60-95°C) processes can be used to inactivate the pectic enzyme and to achieve higher viscosity tomato paste. The study of tomato solids and PG enzyme activity showed that the levels of insoluble solids, total solids, pectin, and °Brix in Ferry Morse tomatoes were independent of fruit ripeness. The amount of PG enzymes was high in orange and dark red tomatoes and the activity of PG enzymes increased as a function of ripeness, from green to dark red. In the dark red tomato, the inactivation of PG enzyme activity was required to retain the level of pectin. Cold break temperatures below 60°C can not inactivate the PG enzyme activity. The PG enzymes started to be denatured when the hot break temperature was above 65°C and be completely destroyed when the break temperature was above 80°C. A mathematical model of the break process was formulated and Matlab programme was used to predict the effect of break temperatures on the pectin and PG enzyme concentration of the tomato pulp in the break tank for any inputs of feed rate (the flow rate to the break tank), feed ripeness, and residence time. The model was used to demonstrate the understanding and the optimisation of break process performance. Longer residence time of dark red tomato pulp in the break tank can decrease pectin fraction residual and increase enzyme inactivation in the tank temperature range 40 to 60°C. The pectin fraction remaining increased when the tank temperature was above 60°C because of the inactivation of PG enzymes. At 80°C there was no effect of residence time, the pectin fraction residual increased and reached 90% and enzyme fraction residual decreased to 10%. The effect of mixed tomato ripeness between the ripe fruit (orange and dark red) with the unripe fruit (green, breaker, and turning), the level of PG enzymes in the break tank decreased and affected on the higher pectin fraction remaining. Lower break temperature can be therefore used in this process to inactivate the low amount of PG enzyme and to achieve the same extent of pectin hydrolysis. The interruption of the feed coming into the break tank during tomato processing can increase the pectin fraction remaining and the enzyme fraction remaining in a new steady state when the feed was turned on.
Keywords: Tomato products